HIV epidemic in fishing communities in Uganda: A scoping review. - Patou Masika Musumari; Teeranee Techasrivichien; Kriengkrai Srithanaviboonchai; Rhoda K Wanyenze; Joseph K B Matovu; Hemant Poudyal; S Pilar Suguimoto; Saman Zamani; Arunrat Tangmunkongvorakul; Masako Ono-Kihara; Masahiro Kihara (PLoS ONE)
Background Fishing communities in many Sub-Saharan African countries are a high-risk population group disproportionately affected by the HIV epidemic. In Uganda, literature on HIV in fishing communities has grown extensively since the first country's documented case of HIV in a fishing community in 1985. The current study describes the status of the HIV burden, prevention, and treatment in Ugandan fishing communities. Method This scoping review was conducted based on the York Framework outlined by Arksey and O'Malley. We searched the PubMed, Embase, and Web of Science databases to identify relevant quantitative and qualitative studies on HIV incidence, HIV prevalence, HIV-related risk factors, HIV testing, antiretroviral therapy coverage and adherence, and interventions to improve treatment outcomes and reduce HIV risk factors. Results & conclusion We identified 52 papers and 2 reports. Thirty-four were quantitative, 17 qualitative, and 3 had a mixed-methods design. Eleven studies reported on the prevalence of HIV and 8 on HIV incidence; 9 studies documented factors associated with HIV incidence or HIV positive status; 10 studies reported on HIV testing coverage and/or associated factors; 7 reported on antiretroviral therapy coverage/adherence/outcomes; and 1 study reported on the impact of combination HIV interventions in fishing communities. This scoping review revealed a significant lack of evidence in terms of what works in HIV prevention and for improving adherence to ART, in contrast to the relatively large amount of evidence from observational quantitative and qualitative studies on HIV prevalence, incidence and related risk factors in Ugandan fishing communities. Intervention studies are urgently needed to fill the current evidence gaps in HIV prevention and ART adherence.